Study the Image of Wasit Subsurface Structure Using 3D Seismic Data – Centre of Iraq - Al-Ridha, Nawal; Ali, Huda (Iraqi Journal of Science, 2025)
This study is about the seismic reflection structural interpretation of the Fatha Formation in Tertiary and Shiranish and Nahr Umr Formations in Cretaceous of Wasit structure , the 3D seismic data volume have been used in the interpretation process based on synthetic traces ,the tops of the three Reflectors s were determined and picked using an interpretation using specialized computer program . After these formations have been traced overall the area the subsurface structural image can be extracted in order to determined were hydrocarbons could possibly exist , Nahr Umr is expected to be a hydrocarbon reservoir in this research .